2015
DOI: 10.1208/s12249-015-0340-y
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to Flurbiprofen Pulsatile Colonic Release: Formulation and Pharmacokinetics of Double-Compression-Coated Mini-Tablets

Abstract: Abstract. A significant plan is executed in the present study to study the effect of double-compression coating on flurbiprofen core mini-tablets to achieve the pulsatile colonic delivery to deliver the drug at a specific time as per the patho-physiological need of the disease that results in improved therapeutic efficacy. In this study, pulsatile double-compression-coated tablets were prepared based on timecontrolled hydroxypropyl methylcellulose K100M inner compression coat and pH-sensitive Eudragit S100 out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…To generate in vitro-in vivo correlation (IVIVC), the in vitro cumulative percent of tacrolimus release of optimized CSP formulation was compared against the extent of in vivo absorption, i.e., cumulative AUC values of the same formulation (Vemula, 2015c).…”
Section: In Vitro-in Vivo Correlationmentioning
confidence: 99%
“…To generate in vitro-in vivo correlation (IVIVC), the in vitro cumulative percent of tacrolimus release of optimized CSP formulation was compared against the extent of in vivo absorption, i.e., cumulative AUC values of the same formulation (Vemula, 2015c).…”
Section: In Vitro-in Vivo Correlationmentioning
confidence: 99%
“…To test the significance of difference between calculated pharmacokinetic parameters of both immediate-release tablet and formulation MP1 statistical analysis using analysis of variance (ANOVA) was done and a P value of P<0.05 was considered statistically significant (Vemula, 2015).…”
Section: Pharmacokinetic Data Analysismentioning
confidence: 99%
“…8 Similarly, Tung et al investigated colon-specific targeted tablets of metronidazole through a pectin/hydroxypropyl methylcellulose dry powder coating. 9 Vemula also reported double-compression-coated mini-tablets for pulsatile colonic release of flurbiprofen, 10 as well as colon-specific pH-and time-dependent tablets. 11 However, only a few studies have reported about colonspecific pulsatile nanodrug delivery systems using advanced technologies.…”
Section: Introductionmentioning
confidence: 99%
“…7 Many efforts have been dedicated to drug colon-targeted pulsatile release through traditional methods on solid dosage forms. [8][9][10][11] Vemula and Katkum reported coated tablets of ketorolac tromethamine, which were prepared using double-compression coating method. 8 Similarly, Tung et al investigated colon-specific targeted tablets of metronidazole through a pectin/hydroxypropyl methylcellulose dry powder coating.…”
Section: Introductionmentioning
confidence: 99%